Influence of artificial sweeteners on the kinetic and metabolic behavior of Lactobacillus delbrueckii subsp. bulgaricus - Manca, Maria Cristina (2007)
The addition of artificial sweeteners to a LAPT (yeast extract, peptone, and tryptone) medium without supplemented sugar increased the growth rate and final biomass of Lactobacillus delbrueckii subsp. bulgaricus YOP 12 isolated from commercial yogurt. Saccharin and cyclamate were consumed during microorganism growth, while the uptake of aspartame began once the medium was glucose depleted. The pH of the media increased as a consequence of the ammonia released into the media supplemented with the sweeteners. The L. delbrueckii subsp. bulgaricus strain was able to grow in the presence of saccharin, cyclamate, or aspartame, and at low sweetener concentrations, the microorganism could utilize cyclamate and aspartame as an energy and carbon source.